Full-diversity design criterion for multi-user STBC based on integer-forcing detection - Guoquan LI; Xiangyun ZHOU; Jinzhao LIN; Yongjun XU; Yu PANG; Jiacheng WANG (Tongxin xuebao)
Multi-user space time block code systems have the problem of high decoding complexity.To ensure good system performance with low decoding complexity at the same time,low complexity integer-forcing (IF) detection algorithm was applied to multi-user space time block code.Then the upper bound of error probability for IF detection was derived by minimizing the equivalent noise power.To obtain good multi-user space time block code when decoded with IF detection,a full-diversity design criterion was proposed.It was proved that full diversity could be achieved if every user’s space time block code had property of non-vanishing singular value.Simulation result shows that the code gain is found related to the minimum singular value.